The NR2F2-HAND2 signaling axis regulates progesterone actions in the uterus at early pregnancy - Oh, Yeongseok; Quiroz, Elvis; Wang, Tianyuan; Medina-Laver, Yassmin; Redecke, Skylar Montague; Dominguez, Francisco; Lydon, John P.; DeMayo, Francesco J.; Wu, San-Pin (Frontiers in Endocrinology, 2023)
Endometrial function is dependent on a tight crosstalk between the epithelial and stromal cells of the endometrium. This communication is critical to ensure a fertile uterus and relies on progesterone and estrogen signaling to prepare a receptive uterus for embryo implantation in early pregnancy. One of the key mediators of this crosstalk is the orphan nuclear receptor NR2F2, which regulates uterine epithelial receptivity and stromal cell differentiation. In order to determine the molecular mechanism regulated by NR2F2, RNAseq analysis was conducted on the uterus of Pgr Cre ;Nr2f2 f/f mice at Day 3.5 of pregnancy. This transcriptomic analysis demonstrated Nr2f2 ablation in Pgr-expressing cells leads to a reduction of Hand2 expression, increased levels of Hand2 downstream effectors Fgf1 and Fgf18, and a transcriptome manifesting suppressed progesterone signaling with an altered immune baseline. ChIPseq analysis conducted on the Day 3.5 pregnant mouse uterus for NR2F2 demonstrated the majority of NR2F2 occupies genomic regions that have H3K27ac and H3K4me1 histone modifications, including the loci of major uterine transcription regulators Hand2, Egr1, and Zbtb16. Furthermore, functional analysis of an NR2F2 occupying site that is conserved between human and mouse was capable to enhance endogenous HAND2 mRNA expression with the CRISPR activator in human endometrial stroma cells. These data establish the NR2F2 dependent regulation of Hand2 in the stroma and identify a cis-acting element for this action. In summary, our findings reveal a role of the NR2F2-HAND2 regulatory axis that determines the uterine transcriptomic pattern in preparation for the endometrial receptivity.